Pengembangan Sistem E-Learning Berbasis Moodle - Alfredo Gormantara; Astrid Lestari Tungadi; Ridnaldy Y Carolus (STMIK Budi Darma, 2023)
Communication and information technology in the world of education is an effort made in creating a different teaching-learning atmosphere so that students can develop their potential. E-Learning is a learning process that utilizes computer technology, computer networks, and the Internet in the process of disseminating knowledge, thus enabling students to learn via computers anywhere without having to physically go to class/lectures. Atma Jaya Makassar University already has an E-Learning system but several obstacles occur starting from a less interactive display, limited functions, no integration with the academic system, and the unavailability of mobile-based E-Learning. Previously, e-learning used a claroline base which had problems in terms of appearance and functionality. This research uses the SDLC (Software Development Life Cycle) method in developing e-learning software. The waterfall method is a work method that emphasizes sequential and systematic phases. This method starts from identifying the problems that occur, the design, implementation, testing and verification stages. Moodle-based E-Learning products offer to enter the